Chemotherapy effect on neglected thyroid carcinoma metastatic to axilla – A case report (Indian Journal of Case Reports, 2021)
Thyroid cancer is a thyroid gland malignancy with an increasing incidence, especially in women aged 25–65 years. The tumor, node, and metastases classification serves to determine cancer management. Here, we report the case of 58 years old who came with complaints of lumps in the neck and the left armpit for 2 months. Based on the results of the systemic history, physical examination, and supporting examinations including X-rays, ultrasound, magnetic resonance imaging, and biopsy, a final diagnosis of T4bN1bM1 thyroid papillary cancer (lung) with a left axillary mass, which is cancer thyroid metastases, was given. The management carried out in these patients was chemotherapy with chemotherapy regimens doxorubicin (20 mg/m2) iv and paclitaxel (60 mg/m2) iv once per week, respectively, but unfortunately, the patient died due to respiratory failure. This case report tries to elaborate the chemotherapy effects on neglected thyroid carcinoma metastatic to the axilla so that the clinicians have representation about these effects.